Safety of BCG vaccination and revaccination in healthcare workers - Paola Villanueva; Nigel W. Crawford; Mariana Garcia Croda; Simone Collopy; Bruno Araújo Jardim; Tyane de Almeida Pinto Jardim; Helen Marshall; Cristina Prat-Aymerich; Alice Sawka; Ketaki Sharma; Darren Troeman; Ushma Wadia; et al. (Human Vaccines & Immunotherapeutics, 2023)
BCG vaccination and revaccination are increasingly being considered for the protection of adolescents and adults against tuberculosis and, more broadly, for the off-target protective immunological effects against other infectious and noninfectious diseases. Within an international randomized controlled trial of BCG vaccination in healthcare workers (the BRACE trial), we evaluated the incidence of local and serious adverse events, as well as the impact of previous BCG vaccination on local injection site reactions (BCG revaccination). Prospectively collected data from 99% (5351/5393) of participants in Australia, Brazil, Spain, The Netherlands and the UK was available for analysis. Most BCG recipients experienced the expected self-limiting local injection site reactions (pain, tenderness, erythema, swelling). BCG injection site itch was an additional common initial local symptom reported in 49% of BCG recipients. Compared to BCG vaccination in BCG-naïve individuals, BCG revaccination was associated with increased frequency of mild injection site reactions, as well as earlier onset and shorter duration of erythema and swelling, which were generally self-limiting. Injection site abscess and regional lymphadenopathy were the most common adverse events and had a benign course. Self-resolution occurred within a month in 80% of abscess cases and 100% of lymphadenopathy cases. At a time when BCG is being increasingly considered for its off-target effects, our findings indicate that BCG vaccination and revaccination have an acceptable safety profile in adults.